Identifikasi Ektoparasit Pada Anjing di Klinik Hewan Kota Kupang - Deta, Stepanus Umbu; Almet, Julianty; Sitompul, Yeremia Yobelanno (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2024)
Dogs have become popular pets due to their high intelligence and loyalty to their owners. Dogs can play a role in the spread of disease through ectoparasite infestation. Ectoparasites are parasites that attack and live their lives on the surface of the host's body. This study aimed to identify ectoparasites infesting dogs in Kupang City veterinary clinics. Collection of ectoparasite samples was carried out on 50 dogs with 10 samples at each clinic in 5 veterinary clinics in Kupang City. Collection results were stored in 70% alcohol, followed by preservation in the form of glass preparations, and observed using a microscope. Data were analyzed descriptively and then displayed in tables and figures. The results of the identification of ectoparasites found in dogs are Ctenocephalides canis, Rhipicephalus sanguineus, Haemaphysalis sp. dan Heterodoxus Sp.